Altered spontaneous brain activity pattern in patients with ophthalmectomy: an resting-state fMRI study - Zhang, Bing (International journal of ophthalmology, 2020)
To use the voxel-wise degree centrality (DC) method to explore the underlying functional network brain-activity in patients with ophthalmectomy. A total of 32 ophthalmic surgery patients (10 women and 22 men), and 32 healthy subjects (10 women and 22 men) highly matched in gender, age, and the same operation method. Everyone experienced a resting-state functional magnetic resonance imaging scan. The spontaneous brain activity could be assessed by DC. Correlation analysis was used to explore the relationships between the average DC signal values and behavior performance in different regions. Receiver operating characteristic (ROC) curve analysis was utilized to differentiate between ophthalmectomy patients and healthy controls (HCs). Compared with HCs, ophthalmectomy patients had greatly reduced DC values in left lingual gyrus, bilateral lingual lobe, left cingulate gyrus, and increased DC values of left cerebellum posterior lobe, left middle frontal gyrus1, right supramarginal gyrus, left middle frontal gyrus2, right middle frontal gyrus. However, we did not find that there was a correlation between the average DC values from various brain regions and clinical manifestations. Dysfunction may be caused by ophthalmectomy in lots of cerebral areas, which may show the potential pathological mechanism of ophthalmectomy and it is beneficial to clinical diagnosis.